mpact of Covid-19 Pandemic on Career Plans and Entrepreneurship Intentions of Students in Muhammadiyah Magelang University - Syaidah, Wulan Dewi Fatikhatus; Nisaa, Urmilla Fakhrun; Maharani, Jasmine Nabila; Setiadi, Namira Assyafira; Husna, Aftina Nurul (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This study aims to determine the effect of student entrepreneurship intentions on career plans due to the impact of the Covid-19 Pandemic. Entrepreneurial intention can be interpreted as a process of seeking information to achieve a business goal. According to data obtained from the central statistics agency, data on the increasing number of unemployed, from 2019 to 2020 increased by 1.84% so that the number of unemployed becomes 7.07%. In addition, the difficulty of finding a job is also one of the causes of someone becoming unemployed. The method used in this study is a quantitative method using a descriptive survey. The participants of this study were